ERROR ANALYSIS ON STUDENTS WRITING NARRATIVE TEXT - Ningsi, Fitri; Nurhidayat,; Pratiwi, Amanda (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the types and frequency of linguistic errors found in narrative texts written by eleventh-grade students of MAN 1 Bima during the 2024/2025 academic year. The research adopts a qualitative descriptive method and applies the Surface Strategy Taxonomy, which classifies errors into omission, addition, misformation, and misordering. Data were collected from students' written narratives based on the story "Cinderella" and analyzed to identify and categorize the errors. The findings reveal a total of 253 errors, with misformation being the most dominant type (77.08%), indicating significant difficulties in students' understanding of appropriate word forms and grammatical structures. Factors contributing to these errors include limited vocabulary, weak grammatical foundation, first language interference, lack of writing practice, and time constraints. The results suggest the need for more contextual grammar instruction, consistent writing practice, and constructive feedback. This research provides insights for educators to design more effective strategies for improving students’ writing competence, particularly in narrative text production.